Simulation of Magnet Thickness and Angle of Attack on Magnetic Force for Magnetic Turbine Design - Pratama, Eka; Wirawan, Wirawan (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Electric motors play a vital role across various industries. As their electricity demand grows, improving efficiency has become a priority. One area of innovation involves the use of magnetic strips for improving performance. This study aims to determine the magnet thickness and the angle of attack position in producing the strongest repulsive force in the magnetic turbine. The study used a simulation using SOLIDWORKS and EMS software, applying neodymium N52 magnets with varying sizes and angles of attack. The results indicate that the most efficient magnetic turbine configuration utilizes rotor and stator magnets with dimensions of Ø10 × 20 mm and an angle of attack of 44°. Magnet thickness influences the magnetic force: Thicker magnets generate stronger repulsive forces due to higher stored magnetic energy, whereas thinner magnets result in weaker forces due to reduced magnetization volume. The simulation of two opposing magnets confirmed that the configuration of Ø10 × 20 mm at a 44° angle of attack produced the highest magnetic flux density of 2.277 × 10⁻¹ Tesla. Furthermore, the 44° angle between rotor and stator yielded a more stable magnetic flux distribution, effectively minimizing cogging torque, that a common cause of undesirable fluctuations in rotor motion. This angle can be recommended for achieving smoother and more efficient turbine operation.